Anatomical Characteristics of Cutaneous Branches Extending From the Second Dorsal Metacarpal Artery - Liu, Peng; Deng, Zhongyuan; Zhang, Tao; Li, Xiaojian (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract Background: The second dorsal metacarpal artery cutaneous branches flap is often used to repair skin defects in the hand. The localization of the cutaneous branch is very critical for the removal of the flap. The purpose of this study was to quantitatively analyze the origin of the cutaneous branches and the distribution characteristics of the radial and ulnar side to provide an anatomical basis for the flap design. Methods: 16 specimens were perfused with latex. 4 specimens were infused with ethyl acetate and plastic, and 4 specimens were perfused with red latex to make pellucid specimens. The origin, travel, and distribution of the cutaneous branches of the second dorsal metacarpal artery were anatomically observed and measure the length of the cutaneous branch from the midpoint of the second web space edge, the diameter and pedicle length of the radial and ulnar distribution of cutaneous branches from the second dorsal metacarpal artery. Results: The cutaneous branches of the second dorsal metacarpal artery were mainly clustered at 3 positions, the second cluster point was at 43.9%, the forth cluster point was at 61.2%, and the fifth cluster point was at 72.1%. The first cluster point was at 30.8% and the sixth cluster point was at 85.6%. The diameter and pedicle length of the sixth cluster point were the largest. There was no significant difference in the distribution of the diameter and pedicle length of the cutaneous branch between the radial and ulnar side. The second dorsal metacarpal artery sends out 1-2 cutaneous branches before the tendon joint, and formed a blood vessel anastomosis with the cutaneous branches farther from the tendon joint. The dorsal branch of the radial nerve in the hand extended a nerve branch at the wrist joint and traveled between the cutaneous branches of the second dorsal metacarpal artery to dominate the corresponding skin. Conclusion: Three clusters in the distal second dorsal metacarpal artery was chose as the flap pedicle with cutaneous nerve to repair the skin defect in the hand and fingers.